2022
DOI: 10.1097/cmr.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

A lead-in safety study followed by a phase 2 clinical trial of dabrafenib, trametinib and hydroxychloroquine in advanced BRAFV600 mutant melanoma patients previously treated with BRAF-/MEK-inhibitors and immune checkpoint inhibitors

Abstract: Patients with advanced BRAFV600 mutant melanoma who progressed on prior treatment with BRAF-/MEK-inhibitors and programmed cell death 1 or cytotoxic T-lymphocyte-associated antigen 4 immune checkpoint inhibitors can benefit from retreatment with the combination of a BRAF- and a MEK-inhibitor (‘rechallenge’). Hydroxychloroquine can prevent autophagy-driven resistance and improve the efficacy of BRAF-/MEK-inhibitors in preclinical melanoma models. This clinical trial investigated the use of combined BRAF-/MEK-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…51 Hydroxychloroquine Populational studies. Within the studies that reported psychiatric adverse effects after HCQ ingestion, anxiety is the most common symptom, 25,32,33 followed by psychotic symptoms 32,33 and insomnia. 30,32 Studies also mentioned that patients developed suicide ideation, 25 self-harm, 32 confusion, 32 disturbance in attention, 31 emotional liability, 31 depression, 30 nervousness, 36 and irritability.…”
Section: Chloroquinementioning
confidence: 99%
See 2 more Smart Citations
“…51 Hydroxychloroquine Populational studies. Within the studies that reported psychiatric adverse effects after HCQ ingestion, anxiety is the most common symptom, 25,32,33 followed by psychotic symptoms 32,33 and insomnia. 30,32 Studies also mentioned that patients developed suicide ideation, 25 self-harm, 32 confusion, 32 disturbance in attention, 31 emotional liability, 31 depression, 30 nervousness, 36 and irritability.…”
Section: Chloroquinementioning
confidence: 99%
“…In a sample of patients with malaria (n = 532), Mittal et al 23 Two randomized open-label clinical trials evaluated the safety and efficacy of HCQ plus imatinib (IM) or dabrafenib (DAB) and trametinib (TRA) in patients with myeloid leukemia and melanoma, respectively. 30,33 The first study concluded that HCQ administration is safe with manageable adverse effects. 30 However, 1 patient from Awada et al 33 study permanently discontinued HCQ treatment due to anxiety/psychotic disorder caused by the drug.…”
Section: Hydroxychloroquinementioning
confidence: 99%
See 1 more Smart Citation
“…A phase I/II trial in advanced BRAFV600-mutant melanoma showed that HCQ in combination with dabrafenib and trametinib every day (D+T) was well tolerated and produced an encouraging response rate (RR) and progression-free survival (PFS) [ 237 ]. Another lead-in safety study followed by a phase II trial of HCQ+D+T in patients with advanced BRAFV600-mutant melanoma also demonstrated that HCQ can prevent autophagy-driven resistance and, therefore, enhance the efficacy of BRAF-/MEK-inhibitor therapy in a “rechallenge” setting [ 238 ]. The addition of HCQ to gemcitabine or nanoparticle albumin-bound paclitaxel (nab-PTX) was also safe, which led to a greater pathological tumor response in patients with resectable pancreatic adenocarcinoma, as shown in a randomized phase II preoperative trial [ 239 ].…”
Section: Autophagy: a Novel Force Triggering Drug Resistancementioning
confidence: 99%
“…Despite the complex interaction between suppressive and supportive roles of autophagy in cancer, the majority of autophagy inhibitors have been proposed as a strategy for improving cancer therapies and considered in some clinical trials. Previous studies have shown that patients with BRAF mutant melanoma regressed after conventional anti-BRAF and chloroquine combination therapy ( Awada et al, 2022 ). These compounds have been identified as cytoprotective autophagy inhibitors by targeting the classical PI3K complex, such as 3-methyladenine (3-MA), Wortmannin, and LY294002, which inhibit the early stage of autophagy, and autolysosomes, like chloroquine (CQ), hydroxychloroquine (HCQ), and bafilomycin A1, which primarily inhibit the late stage of autophagy ( Bao et al, 2018 ; Collins et al, 2018 ; Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%